PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA KACER TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA - Khoiruzzad, Asif; Erna Zumrotun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The importance of critical thinking in education cannot be overstated. Yet, students often demonstrate minimal involvement in their learning journey, showing a tendency to remain passive. Hence, this study aimed to explore how Problem-Based Learning (PBL) aided by the 'kacer' (white-rumped shama) media affects students' critical thinking skills. Employing a pre-experimental design method, specifically the